Comparison of influence of gold contamination on the performances of planar and three dimensional c-Si solar cells. (November 2019) - Baytemir, Gulsen; Es, Firat; Turan, Rasit
Abstract: Radial junction solar cell is proposed as an alternative device geometry to planar junction solar cell due to its superior electro-optical performance. In this geometry, densely-packed micropillars enable the collection of minority carriers in the radial direction. Thus, the distance that carriers should travel to reach the p-n junction is shortened, allowing the use of low quality materials with poor carrier lifetime. In this study, we have experimentally studied the advantage of radial junction approach in low quality Si. For this purpose, we fabricated planar and radial junction solar cells using Si wafers with Au impurities. Average efficiency values of 15.74% and 15.66% were obtained for planar and radial cells in uncontaminated samples, respectively, indicating that close efficiency values were obtained when using high-quality materials. However, in the case of contamination, the efficiency of the cells with radial junction degraded less compared to the planar junction with the values of 14.71% and 12.72%, respectively. This is consistent with the expectation that radial junction cells are less sensitive to the quality of the material used. Moreover, these results, together with future structural optimization, lay a solid foundation for lowering fabrication costs without reducing the performance of the solar cell. Highlights: High electro-optical performance radial junction over planar junction for solar cells. Densely packed nano/micropillars allow the carrier collection in the radial direction. Metal impurities affect the solar cell performance by increasing recombination. c-Si wafers contaminated with Au impurities were used in solar cell fabrication. The efficiencies of the RJSC are less sensitive to the quality of the material used.